Allelic Mutations of KITLG, Encoding KIT Ligand, Cause Asymmetric and Unilateral Hearing Loss and Waardenburg Syndrome Type 2 - Zazo Seco, Celia; Serrao de Castro, Luciana; van Nierop, Josephine W.; Morín, Matías; Jhangiani, Shalini; Verver, Eva J.J.; Schraders, Margit; Maiwald, Nadine; Wesdorp, Mieke; Venselaar, Hanka; Spruijt, Liesbeth; Oostrik, Jaap; et al. (My University, 2015)
Linkage analysis combined with whole-exome sequencing in a large family with congenital and stable non-syndromic unilateral and asymmetric hearing loss (NS-UHL/AHL) revealed a heterozygous truncating mutation, c.286_303delinsT (p.Ser96Ter), in KITLG. This mu tation co-segregated with NS-UHL/AHL as a dominant trait with reduced penetrance. By screening a panel of probands with NS-UHL/AHL, we found an additional mutation, c.200_202del (p.His67_Cys68delinsArg). In vitro studies revealed that the p.His67_Cys68delinsArg transmembrane isoform of KITLG is not detectable at the cell membrane, supporting pathogenicity. KITLG encodes a ligand for the KIT receptor. Also, KITLG-KIT signaling and MITF are suggested to mutually interact in melanocyte development. Because mutations in MITF are causative of Waardenburg syndrome type 2 (WS2), we screened KITLG in suspected WS2-affected probands. A heterozygous missense mutation, c.310C>G (p.Leu104Val), that segregated with WS2 was identified in a small family. In vitro studies revealed that the p.Leu104Val transmembrane isoform of KITLG is located at the cell membrane, as is wild-type KITLG. However, in culture media of transfected cells, the p.Leu104Val soluble isoform of KITLG was reduced, and no soluble p.His67_Cys68delinsArg and p.Ser96Ter KITLG could be detected. These data suggest that mutations in KITLG associated with NS-UHL/AHL have a loss-of-function effect. We speculate that the mechanism of the mutation underlyingWS2 and leading to membrane incorporation and reduced secretion of KITLG occurs via a dominant-negative or gain-of-function effect. Our study unveils different phenotypes associated with KITLG, previously associated with pigmentation abnormalities, and will thereby improve the genetic counseling given to individuals with KITLG variants.